ERTEKLERDIŃ TIPOLOGIYALÍQ ÓZGESHELIKLERI - Qazaxbaev, S.S. (ILIM hám JÁMIYET, 2024)
In the article, the typological features, similarities, themes, genre features, system of images, plots, motives of fairy tales in world children's literature are discussed on a typological basis.